2007
DOI: 10.1074/jbc.m609730200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Plant-like Protochlorophyllide a Divinyl Reductase in Green Sulfur Bacteria

Abstract: The green sulfur bacterium Chlorobium tepidum synthesizes three types of (bacterio)chlorophyll ((B)Chl): BChl a P , Chl a PD , and BChl c F . During the synthesis of all three molecules, a C-8 vinyl substituent is reduced to an ethyl group, and in the case of BChl c F , the C-8 2 carbon of this ethyl group is subsequently methylated once or twice by the radical S-adenosylmethionine enzyme BchQ. The C. tepidum genome contains homologs of two genes, bchJ (CT2014) and CT1063, that are highly homologous to genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
66
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 30 publications
3
66
0
Order By: Relevance
“…Chew and Bryant (2007) confirmed the presence of the corresponding enzyme in a green sulfur bacterium, C. tepidum TL3 (CT1063). On the other hand, Nagata et al (2005) could not identify DVR homologues in most cyanobacteria.…”
Section: Phylogenetic Analysis Of Slr1923 Homologues and Their Distrisupporting
confidence: 56%
See 3 more Smart Citations
“…Chew and Bryant (2007) confirmed the presence of the corresponding enzyme in a green sulfur bacterium, C. tepidum TL3 (CT1063). On the other hand, Nagata et al (2005) could not identify DVR homologues in most cyanobacteria.…”
Section: Phylogenetic Analysis Of Slr1923 Homologues and Their Distrisupporting
confidence: 56%
“…It is also found in the green sulfur bacterium C. tepidum TLS (Chew and Bryant, 2007). However, it was not found in other cyanobacteria.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In an early study using the purple bacterium Rhodobacter capsulatus, the mutational analysis judged that a bchJ gene encodes one of the subunits for DVR (4,11). However, recent investigations have indicated that BchJ is not DVR and would be a scaffold or chaperone protein for an unidentified route among several biosynthetic steps from 8V-PChlide a to BChl a (8,12). In the case of Chl a synthesis, a AT5G18660 gene of the higher plant Arabidopsis thaliana was identified as a DVR gene because the gene mutant accumulated 8-vinyl-Chls (8V-Chls) a and b (13,14); hereafter in this work, this DVR is called planttype DVR.…”
mentioning
confidence: 99%